Pengalaman Haid Pertama Santri Putri Setelah Pembelajaran Kitab Risalatul Mahid di Madrasah Diniyah Roudlotul Huda Kebumen - Apriliani, Titi; Khasanah, Nginayatul (IAINU Kebumen, 2024)
This research has the objectives (1) To find out the learning of the book Risalatul Mahiḍ in the shifir class C Madrasah Roudlotul Huda Kebumen; (2) To find out the experience of female students' first menstruation after studying the Risalatul Mahiḍ Book in the shifir class C of Madrasah Diniyah Roudlotul Huda Kebumen. The research method uses a descriptive qualitative method with a data collection process through observation, interviews and documentation of Madrasah Diniyah Roudlotul Huda learning activities as well as the experiences of the first menstruation of female students in class C class. The data analysis techniques used are data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that: (1) Learning the book Risalatul Mahiḍ in the shifir class C Madrasah Roudlotul Huda Kebumen has a specific aim to study the menstrual laws contained in the book Risalatul Mahiḍ. Using the lecture method with the learning process including preparation before teaching, implementation of learning activities, and evaluation of learning. (2) The experience of female students in class C when experiencing their first menstruation is that they feel afraid, anxious and embarrassed for reasons such as experiencing menstruation while at the Islamic boarding school. After studying the book Risalatul Mahiḍ in class C, the students had a good learning experience and were able to understand the laws of menstrual blood better than before.